Reliability and preliminary reference values for the Total Faulty Breathing Scale (TFBS): A cross‐sectional study. Issue 3 (24th May 2022) - Mohan, Vikram; Branney, Jonathan; Clark, Carol; Neal, Rebecca; Jagannathan, Madhanagopal; Paungmali, Aatit; Perri, Maria
Abstract: Background and Aims: The evaluation of breathing function is crucial in the clinical examination of the respiratory system. The Total Faulty Breathing Scale (TFBS) could be used in clinical settings to quantify the measurement of breathing dysfunction. Reliability data for the TFBS are available for males, but there is a requirement to determine reliability for females and to develop reference values. The aim of this study, therefore, was to determine the reliability in females and to establish the preliminary reference values for the TFBS. Methods: Twenty‐three healthy female participants for reliability and 44 (7 male and 37 female) participants for preliminary reference values participated in this cross‐sectional study. For both aspects of the study, participants were instructed to breathe at their own pace with no specific instruction. Then each participant was observed carrying out normal breathing for a period of 10 breaths and deep breathing for a period of 10 breaths while being assessed with the TFBS. Results: Intrarater and interrater reliability of the TFBS showed a kappa value of 0.769 and 0.751, respectively, indicating substantial agreement for female participants. The preliminary reference categories for TFBS were reported to be normal for 20 (45.5%) participants and mild faulty breathing for the remaining 24 (54.4%) participants. Conclusions: The findings of this study suggested that TFBS was reliable to measure breathing function among female participants, and the reference categories may be helpful in the identification of normal and faulty breathing.